Study of Treatment in Heart Disease Patients Installation in Undata Hospital, Central Sulawesi - Niluh Puspita Dewi; Indah Kurnia Utami; Al'vira Gunawan; Muh. Thamrin Tahir; Syafika Alaydrus; Nani Astria Polontalo (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: Heart diseasesis a disorder of heart functionsdue to lack of bloods in the heart muscles due to narrowingsof the coronary artery. The purposesof this study was to describe t he characteristics and use of heart disease drugs based on parameters of rationality of drug use in Undata Hospital, Central Sulawesi Province including gender, age, heart drug class, complementary drug class, length of hospitalization, laboratory data, comorbidities , appropriate indications, the right drugs and the right dose. Methods: This researchsis a non-experimental type of research conducted prospectively during February-April 2022. The sampling technique in this study was purposive sampling, namely sampling based on established criteria. All samples that met the requirements who came to the hospital were used as research samples according to the required sample size of 40 respondents and based on the available data collection time. Results: The results of the study were 40 patients with hearts disease, the most heart disease sufferers were male with a percentage of 67.5%, in the age range of 56-65 years 32.5%, the most commonly used companion drug was Alprazolam as much as 17%, the most length of hospitalization was 4-6 days (55%), the most laboratory results were Hemoglobin/HGB examination as many as 21 patients (14.38%), the most comorbidities namely Hypertension with a percentage of 60% Conclusion: Appropriate use of heart disease drugs based on drug rational parameters in hospitals Undata of the right indication 100%, the right drug selection 100% and the right dose 100%. Recommendedsfor further researchersscan conduct research on cardiac drug interactions.